Effectiveness Of Skincare Therapy And Topical Treatment In The Management Of Perioral Dermatitis At Geps Aesthetic Clinic - Fitri Tri Mulyani; Retno Indrastiti; Rifka Widianingrum (International Journal of Health Engineering and Technology, 2026)
Effectiveness of Skincare Therapy and Topical Treatment in the Management of Perioral Dermatitis at Geps Aesthetic Clinic.Perioral dermatitis (PDO) is an inflammatory skin disease characterized by erythema, papules, and pustules around the mouth. Skincare and topical treatments are often used to reduce inflammation and improve the skin barrier, but the effectiveness of their combination in reducing the severity of DPO is rarely evaluated. This study aims to analyze the effectiveness of skincare and topical treatments in the management of DPO at Geps Aesthetic Clinic. The study used an observational analytical design with a quantitative approach based on medical records. The sample consisted of 68 patients from January 2024–April 2025 using a total sampling technique. Severity was assessed using the Perioral Dermatitis Severity Index (PODSI) from month 0 to month 3 and analyzed using the Mann–Whitney test. The results showed a significant decrease in PODSI scores in the first (p<0.001), second (p=0.043), and third (p<0.001) months. In the third month, 72.1% of patients were in the mild category and 2.9% were in the severe category. The combination therapy was effective in gradually reducing the severity of DPO over three months.